Pendekatan Saving Mothers Giving Life (SMGL) untuk Mencegah Komplikasi Ibu Post Partum - Jaya, Herawati; Rosnani, Rosnani; Ningsih, Ratna; Wahyuni, Sari (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2023)
The most common complication that occurs in developing countries is bleeding, namely 27% (UNICEF, 2015). One of the post partum psychological disorders in Indonesia is baby blues, which is 0.9% (Banlitbangkes, 2018). One of the factors causing low utilization of maternal health services is cultural practices (WHO, 2018). The proportion of people who use traditional health services in Indonesia is 31.4% and those who use traditional health workers is 98.5%. The proportion of utilization of traditional health services in South Sumatra is 29.5%. Then the number of people who ask for help from traditional health workers is very high, namely 98.4% (Banlitbangkes, 2018). Community service results show that the health cadre team experienced increased knowledge and post partum maternal health problems were controlled by all mothers in Pegayut Village who gave birth and made postpartum visits to the village midwife. It can be concluded that the Saving Mothers Giving Life (SMGL) approach is a multi-system approach to reduce maternal mortality and to prevent post-partum maternal complications in Pegayut village. The most common complication that occurs in developing countries is bleeding, namely 27% (UNICEF, 2015). One of the post partum psychological disorders in Indonesia is baby blues, which is 0.9% (Banlitbangkes, 2018). One of the factors causing low utilization of maternal health services is cultural practices (WHO, 2018). The proportion of people who use traditional health services in Indonesia is 31.4% and those who use traditional health workers is 98.5%. The proportion of utilization of traditional health services in South Sumatra is 29.5%. Then the number of people who ask for help from traditional health workers is very high, namely 98.4% (Banlitbangkes, 2018). Community service results show that the health cadre team experienced increased knowledge and post partum maternal health problems were controlled by all mothers in Pegayut Village who gave birth and made postpartum visits to the village midwife. It can be concluded that the Saving Mothers Giving Life (SMGL) approach is a multi-system approach to reduce maternal mortality and to prevent post-partum maternal complications in Pegayut village.